Integrating GIS and NetLogo-based modelling for simulating land-cover change scenarios in Mashhad Metropolitan Area, Iran - Baghban Khiabani, Sajedeh; Rahnama, Mohammad Rahim; Ajza Shokuhi, Mohammad (Bulletin of Geography. Socio-economic Series, 2025)
This paper presents an agent-based model (ABM) integrated with GIS and NetLogo to simulate land-cover changes in the Mashhad Metropolitan Area (MMA) of Northeast Iran until 2030. It has two main objectives: first, to monitor land-cover changes from 2000 to 2020 using the Support Vector Machine (SVM) algorithm, which reveals an increase in built-up areas of 21,303 hectares (58.92%), alongside decreases in barren lands and green spaces of 15,922 hectares (25.73%) and 7,229 hectares (15.86%), respectively. Second, it conducts spatial simulations of land-cover changes projected for 2030 through the ABM in NetLogo, exploring four scenarios. Results indicate that Mashhad is expanding toward the north and west, with informal settlements encroaching on green spaces, while improved road access is expected to further accelerate urban land expansion.